Special Stains Used in Histopathological Techniques: A Brief View - Tariq Soyab (Indian Journal of Forensic Medicine & Toxicology, 2020)
The routine staining which is also called as H & E staining (Hematoxylin and eosin) is the most widely usedstain in the laboratories or histopathology laboratory. In this procedure the nuclear protein stains purpleand the cytoplasm and any other substances stains as red or orange. It plays a very crucial role in medicaldiagnosis or research where the specimen or tissue is been sent for processing. The staining procedure isperformed by trained professionals and after which the role of highly trained pathologists and researcherscome, which under the microscope view the specific structures, cells and even microorganisms to providea diagnosis for the specific disease. The special stains are those which come under the special stainingtechnique or alternative method for the H & E stains, where H & E staining does not provide the properidentification or appreciation of certain normal and abnormal tissue or structure which the pathologist orresearchers needs. This article throws light on the Special stains which are been used in histopathologicalprocedures in which these abnormal or normal tissues can be properly appreciated. The article also focuseson the procedure, principle and uses of these special stains in their respective field.